Design and application of multi-absorption and highly sensitive monolayer graphene microstructure absorption devices located at terahertz frequencies - Guo, Xuncen; Tang, Chaojun; Yi, Zao; Cheng, Shubo; Wang, Junqiao; Li, Boxun (Current applied physics, 2025)
A graphene absorber has been designed in this message that is based on surface plasmon resonance (SPR). The absorber exhibits four perfect absorption peaks within the target frequency band, featuring an innovative structure with excellent tunability and incident-angle insensitivity. The absorber features a triple-layered framework, with a gold (Au) substrate as the bottom layer, a silica (SiO2) layer serving as the medium layer in the middle, and a graphene layer in a “#” symbol shape at the top. The absorber has a simple structure and is easy to fabricate. We then analyzed four variant that the absorber displays peak absorption efficiencies of 99.99 %, 99.32 %, 99.71 %, and 99.99 % when the frequencies are 7.5005 THz, 9.0920 THz, 10.1181 THz, and 11.3193 THz, respectively, all exceeding 99 %, demonstrating excellent absorption performance. Additionally, we set up four electric field monitors to plot the electric field energy distribution maps for the four absorption peaks. We then analyzed four variant structures derived from the original design, comparing the number of absorption peaks, absorption rates, and sensitivity, and concluded that the model structure proposed in this study is optimal. After changing Fermi degree and time of relaxation, adjustment of the waves can be realized. The absorber demonstrates insensitivity to the angle as the incidence angle is changed from 0° to 60°. Furthermore, with the change of environmental refractive index, the maximum sensitivity among peaks can reach 3586 THz/RIU, showcasing high sensitivity. Finally, we calculated the figure of merit (FOM) and quality factor (Q) values for our model, which we compared with those of other absorbers, concluding that our absorber performs exceptionally well in terms of FOM and Q values. Given these advantages, the absorber designed in this paper can be used in fields of sensors etc. [Display omitted] •The graphene absorber based on the SPR effect exhibits four perfect absorption peaks in the 7–12 THz range, with an average absorption rate of 99.61 %.•After tuning the Fermi level and relaxation time, it is demonstrated that the model has good tunability under variations of both parameters.•The sensitivity of the absorption peaks can reach up to 3586.75 GHz/RIU. Comparing the S value, Q value, and FOM value with other models in the literature, our designed structure shows greater application potential and developmental significance.•Within the range of 0–60° for the angle of incidence, the model exhibits insensitivity to angle variations.•The model has been extended, and by comparing four extended structures, it is proven that the designed model possesses excellent absorptivity.